Visual Construction of Logical AND and NAND Gates - Xiyuan Wang; Zhixiang Yin; Zhen Tang; Jing Yang; Jianzhong Cui; Rujie Xu (Journal of Chemistry)
DNA logic gates are an important branch of DNA computing and have a wide range of applications in DNA computing. In this study, logic circuits of AND gate and NAND gate are built on origami substrate. The realization of AND gate uses polymerase strand displacement (PSD) reaction and hybridization chain reaction (HCR). If there is a fluorescent band “1” displayed, the result is true. The realization of the NAND gate requires a cyclic reaction. If there is a fluorescent band “A” or “T” displayed, the result is true; if no fluorescent band is displayed, the result is false.